Anthropology in Norway Directions, Locations, Relations - Bendixsen, Synnøve K.N; Hviding, Edvard (The RAI Country Series, 2021)
Norway, it is claimed, has the most social anthropologists per capita of any country. Well connected and resourced, the discipline - standing apart from the British and American centres of anthropology - is well placed to offer critical reflection. In this book, an inclusive cast, from PhDs to professors, debate the complexities of anthropology as practised in Norway today and in the past. Norwegian anthropologists have long made public engagement a priority - whether Carl Lumholz collecting for museums from 1880; activists protesting with the Sámi in 1980; or in numerous recent contributions to international development. Contributors explore the challenges of remaining socially relevant, of working in an egalitarian society that de-emphasizes difference, and of changing relations to the state, in the context of a turn against multi-culturalism. It is perhaps above all a commitment to time-consuming, long-term fieldwork that provides a shared sense of identity for this admirably diverse discipline.